1995
DOI: 10.1177/0044118x95026003001
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Involvement and the Development of Gender Expectations in Sons and Daughters

Abstract: Data from the National Survey of Children (Waves 1 and 3), a longitudinal survey of 2,000 children who were between the ages of 7 and 11 during the first wave in 1976 and between the ages of 16 and 20 during the third wave in 1987, were analyzed to examine the impact of paternal involvement during childhood as well as the ongoing father-child relationship on sons' and daughters' gender role orientations and attitudes in young adulthood. The results indicated that, compared to females, males placed more importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Erb and Smith (1986) and Moffat (1992) found that gender differences in attitudes toward science exist in our educational process. The consequences in attitudes toward science can be observed in differential course enrollment (Hardesty, 1992; Harpole, 1987; Tippins, 1991), lower female science achievement scores (McNeil & Butts, 1981) and fewer females in science‐related careers (Kahle, 1984; Moffat, 1992). Females are not receiving the same science education and experiences as males (Baker, 1988; Kahle, 1984; Rosser, 1988).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Erb and Smith (1986) and Moffat (1992) found that gender differences in attitudes toward science exist in our educational process. The consequences in attitudes toward science can be observed in differential course enrollment (Hardesty, 1992; Harpole, 1987; Tippins, 1991), lower female science achievement scores (McNeil & Butts, 1981) and fewer females in science‐related careers (Kahle, 1984; Moffat, 1992). Females are not receiving the same science education and experiences as males (Baker, 1988; Kahle, 1984; Rosser, 1988).…”
mentioning
confidence: 99%
“…Females are not receiving the same science education and experiences as males (Baker, 1988; Kahle, 1984; Rosser, 1988). Fewer female students than males are choosing to take elective science classes (Hardesty, 1992; Harpole, 1987; Tippins, 1991). This lack of preparation in science may contribute to the relative exclusion of women from scientific fields and can affect our national economy.…”
mentioning
confidence: 99%